APPLICATION OF SINMAP AND ANALYSIS OF MODEL SENSITIVITY – CASE STUDIES FROM GERMANY AND CHINA - BENNI THIEBES; RAINER BELL; THOMAS GLADE; JIAN WANG; SHIBIAO BAI (Revue Roumaine de Géographie)
Landslides cause significant damage in many parts of the world and consequently many efforts have been made to forecast the spatial probability of future slope failures. In particular regional landslide susceptibility and hazard models have become popular over the last years because they delineate areas which are likely to experience slope failures in the future, which is important, e.g. for spatial planning purposes. In this study, the physically-based model SINMAP (Stability Index Mapping) was applied to two study areas with different geo-environmental conditions; one in the Swabian Alb, Germany, and one in Youfang catchment, Wudu county, Western China. A sensitivity analysis of the geotechnical input parameters was carried out to determine their influence on model outputs. The results show that the majority of observed landslides are located within areas that have been classified as likely to experience slope failure. The spatial resolution of input data has an effect on SINMAP results, however, the difference between 10 m and 30 m data was found to be relatively small. Sensitivity analysis revealed that internal friction has a large influence on susceptibility modelling, while the hydrological parameter T/R only changed the results to a very small extent under the parameter range tested in this study. Based on the results it can be concluded that SINMAP is capable of appropriately computing regional landslide susceptibility for large areas and can provide useful information, especially when high detail topography data is available. The results of sensitivity analysis can be expected to be helpful for other researchers for a more successful application of SINMAP to other study areas.